Mediterranean Europe(s)
1 online resource.
Keywords: "This book investigates how ideas of and discourses about Europe have been affected by images of the Mediterranean Sea and its many worlds from the nineteenth century onwards. Surprisingly, modern scholars have often neglected such an influence and, in fact, in most histories of the idea of Europe the Mediterranean is conspicuously absent. This might partly be explained by the fact that historians have often identified Europe with modernity (and the Atlantic world) and, therefore, in opposition to the classical world (centred around the Mediterranean). This book will challenge such views, showing that a plethora of thinkers, from the early nineteenth century to the present, have refused to relegate the Mediterranean to the past. Importance is given to the idea of a distinct 'meridian thought', a notion first set forth by Albert Camus and now reworked by French and Italian thinkers. As most chapters argue, this might represent an important tool for rethinking the Mediterranean and, in turn, it might help us challenge received notions about European identity and rethink Europe as the locus of 'modernity'. Mediterranean Europe(s): Rethinking Europe from its Southern Shores will appeal to researchers and students alike interested in European studies and Mediterranean history"--